Optimal Liability when Consumers Mispredict Product Usage - Andrzej Baniak; Peter Grajzl (Center for Economic Studies and ifo Institute (CESifo), 2016)
We contrast alternative liability rules for social control of product risks when heterogeneous consumers considering purchasing a durable good due to cognitive errors and biases mispredict future product benefits and, thus, the extent of future product usage. Since the expected consumer harm directly depends on the level of product usage, the consequences of consumers' mispredictions vary with the prevailing liability regime. We first characterize the consumers' purchasing decision and the equilibrium levels of safety and activity from the product's usage under no liability, strict liability, and negligence rule. We then compare the three legal regimes from the social welfare standpoint. Our analysis clarifies why and how the choice of the socially optimal legal regime depends on the distribution of consumers based on the direction and extent of their mispredictions. When consumers are susceptible to mispredicting future product benefits and usage, the appropriate legal regime is likely product-specific.
Keywords: K13; D03; D61; 330; misprediction; activity; durable consumer products; product risk; liability rules